Harmonisasi Hukum Ketenagakerjaan Nasional dengan Standar Hukum Perburuhan Internasional - Riska Amelia Putri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Economic globalization has significantly transformed patterns of labor relations and expanded cross-border labor mobility. These developments necessitate alignment between national labor laws and international labor standards. The International Labour Organization plays a leading role in establishing global standards through various labor conventions and recommendations. This study aims to examine the concept of harmonizing national labor laws with international standards, assess its implementation in Indonesia, and identify the challenges faced. The study employs a normative legal method using legislative, conceptual, and comparative approaches. The results indicate that Indonesia has adopted most international standards; however, implementation still faces structural, cultural, and economic obstacles. Legal harmonization is a strategic step to enhance worker protection while maintaining national economic competitiveness.